Kollaborative Innovationen Die innerbetriebliche Nutzung externer Wissensbestände in vernetzten Entwicklungsprozessen - Heidenreich, Martin; Kädtler, Jürgen; Mattes, Jannika (Universitätsverlag Göttingen, 2017)
Innovation is increasingly based on distributed knowledge sources, given that firms often do not possess all competencies necessary for fundamental innovations. Hence, the manner in which firms organize the access to external knowledge and make use of this knowledge in internal innovation processes is crucial for the success of innovation. Learning processes have to be organized across organizational, spa¬tial, functional, and disciplinary boundaries - in particular with regard to colla¬bo¬ra¬tion between knowledge producing and knowledge using firms, suppliers, clients, diverse knowledge based service providers, or research and development centers and universities. The crucial point is how external knowledge gathered in these collaborations can be used within the organization. At this juncture, a specific recontextualization prob¬lem arises for firms, because the successful adoption of externally created knowledge depends on shared experiences of actors and the specific context of the organization where the knowledge has been created. Therefore, externally created knowledge whichmay be incorporated into routines, products, services, and documents has to be (re-)contextualized and recombined using context specific and subjective ex¬pe¬riences, perceptions, and capabilities of the involved actors. It is the solution of re¬contextualization problems that poses the particular challenge of collaborative in¬no¬vation processes. The research project »Collaborative Innovations« (COLLIN) started from the assumption that hierarchical, market, network, and community based forms of go¬vernance play a crucial role for the adoption of external knowledge. Due to their different characteristics with regard to the access to the formation process of the external knowledge as well as the proprietary use of the acquired knowledge the respective governance forms facilitate different ways of dealing with external know¬ledge in collaborative innovation processes.